2007
DOI: 10.1017/s0033291707000980
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influences on obsessive-compulsive symptoms in adults: a population-based twin-family study

Abstract: Background. The contribution of genetic factors to obsessive-compulsive (OC) symptoms has not been examined using a large population-based sample of adults. Furthermore, the extent to which there are qualitative and quantitative differences in genetic architecture between men and women with OC symptoms has not been elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
44
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 59 publications
(80 reference statements)
8
44
5
Order By: Relevance
“…First, in slight contrast to the previous longitudinal study in children (van Grootheest et al, 2007b), we found no quantitative sex differences in average OC scores or heritability estimates in this adult sample, with the same additive genetic factors influencing both males and females.…”
Section: Discussioncontrasting
confidence: 99%
“…First, in slight contrast to the previous longitudinal study in children (van Grootheest et al, 2007b), we found no quantitative sex differences in average OC scores or heritability estimates in this adult sample, with the same additive genetic factors influencing both males and females.…”
Section: Discussioncontrasting
confidence: 99%
“…Error variance cannot be distinguished from nonshared or individual-specific environment, and therefore it is likely that the impact of genetic influence on the etiology of OCS is underestimated. Second, the present study only included women, so results cannot be assumed to hold equally for males, although Van Grootheest et al [2007] recently found in a large twin-family study, that the same genetic risk factors were expressed in men and women for OC behavior. Third, because of the use of a threshold model [Derks et al, 2004], and the fact that number of MZ twins exceeded the number of DZ twins [Posthuma and Boomsma, 2000], the power to distinguish genetic influences from shared environmental influences was moderate.…”
Section: Discussionmentioning
confidence: 91%
“…Heritabilities of 33% and 26% for obsessions and compulsions, respectively, were found. Recently, Van Grootheest et al [2007] obtained the Young Adult Self Report Obsessive-Compulsive Subscale from a group of 5893 mono-and dizygotic twins, and 1,304 additional siblings and found a moderate heritability of 39% for men and 50% for women.…”
Section: Introductionmentioning
confidence: 99%
“…OCD is moderately heritable (Hudziak et al, 2004;Van Grootheest et al, 2007), with heritability rates between 40 and 45% (Hudziak et al, 2004) and first degree relatives of the patients having a 4-10 times higher risk of developing OCD (Nestadt et al, 2000), depending on age of the proband. At the same time, the genetic basis of OCD is complex, multi-factorial, and under strong environmental influence (Grisham et al, 2008).…”
Section: Introductionmentioning
confidence: 99%